Engaging older adults with modern technology internet use and information access needs - Zheng, Robert Z. 1958-; Hill, Robert D.; Gardner, Michael K. (Premier reference source, 2013)
"This book takes a structured approach to the research in aging and digital technology in which older adults’ use of internet and other forms of digital technologies is studied through the lenses of cognitive functioning, motivation, and affordability of new technology" - Provided by publisher